2006
DOI: 10.2134/agronj2005.0164
|View full text |Cite
|
Sign up to set email alerts
|

Univariate Distribution Analysis to Evaluate Variable Rate Fertilization

Abstract: Technological advances in precision fertilization such as yield monitors and remote sensing are increasing the density of samples collected and decreasing the scale inputs can be managed in the field. A compounding problem is that fertilizer applications can often be made at a much smaller scale than yield data can be collected. Analytical tools such as ANOVA and geostatistics can be used on high-density data sets; however, these analytical tools do not provide all the information required to test research ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…According to Freitas (2000), the practical use of bacteria as inoculants requires more experiments because the effects of bacteria on yield and N assimilation of wheat are not well understood. An increase in the N concentration of wheat produces spectral reflectance changes that may be detected by remote sensing instruments, as demonstrated by several researchers (Serrano et al, 2000; Mullen et al, 2003; Pena‐Yewtukhiw et al, 2006; Shou et al, 2007; Sripada et al, 2007; Tilling et al, 2007; Feng et al, 2008). If bacteria treatment affects yield and N assimilation of wheat, it may affect their relationships with spectral parameters.…”
mentioning
confidence: 84%
“…According to Freitas (2000), the practical use of bacteria as inoculants requires more experiments because the effects of bacteria on yield and N assimilation of wheat are not well understood. An increase in the N concentration of wheat produces spectral reflectance changes that may be detected by remote sensing instruments, as demonstrated by several researchers (Serrano et al, 2000; Mullen et al, 2003; Pena‐Yewtukhiw et al, 2006; Shou et al, 2007; Sripada et al, 2007; Tilling et al, 2007; Feng et al, 2008). If bacteria treatment affects yield and N assimilation of wheat, it may affect their relationships with spectral parameters.…”
mentioning
confidence: 84%
“…They found NDVI_GS measurements from growth stages V5-V9 were the most useful and appropriate for making in-season management decisions for corn production. Pena-Yewtukhiwa et al (2006) stressed the importance of the statistical distribution and summary statistics in the study of processes generating NDVI data. The summary statistics are important in the design of algorithms for fertilizer application.…”
Section: Introductionmentioning
confidence: 99%
“…The summary statistics are important in the design of algorithms for fertilizer application. The algorithms divide the data into classes, and then treat each class with a particular rate of fertilizer N. Uniform N rates do not change existing crop variability patterns (Pena-Yewtukhiwa et al 2006). Welsh et al (2003aWelsh et al ( , 2003b found that the most effective variable-rate N strategy for winter barley and wheat was to apply additional N to areas of low shoot density and to reduce N applications to areas of high density.…”
Section: Introductionmentioning
confidence: 99%
“…Each sensor's NDVI readings were individually evaluated. In 2004, univariate statistical analysis (Pena‐Yewtukhiw et al, 2006) found seven significantly different sensor groups (Table 2), with sensor 8 consistently giving the highest NDVI readings and sensor 5 the smallest. The origin and consistency of the observed difference in sensor output in 2004 was not clear.…”
Section: Resultsmentioning
confidence: 99%